Review of Power System Expansion Planning in Vietnam - Pereira, Mario (World Bank, Washington, DC, 2013)
This report assesses current energy expansion planning practices in Vietnam. This assessment comprises both technical aspects (methodology, planning criteria, construction of scenarios, sensitivity analysis and others) and evaluation of recent planning studies. In addition to an assessment of planning practices, it includes proposing a number of scenarios for the local consultant to carry out least cost runs, including lower rates of demand growth, different fuel price assumptions and delays in plant construction, to assess the viability of specific projects without forcing them into the system plan. This report is the deliverable for Task 1, with an overview and comments of current practices for system expansion planning, hydropower and thermal power planning in Vietnam. The report also covers Task 2, by proposing and agreeing scenarios after meetings with IoE. Chapters 2 through 5 describe the current planning practices and the basic components and assumption of the IoE planning scenarios and outputs, namely: (i) load scenario; (ii) planning guidelines; (iii) planning objective and computational tools; and (iv) generation expansion plan. Chapter 6 presents suggestions for sensitivity scenarios, used to evaluate the competitiveness of the Trung Son hydro project and the Nghi Son thermal project.